2019
DOI: 10.1039/c9ra02749a
|View full text |Cite
|
Sign up to set email alerts
|

An overview on synthetic strategies for the construction of star-shaped molecules

Abstract: This review summarizes the strategies for the synthesis of star-shaped molecules as well as their specific syntheses.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

1
8

Authors

Journals

citations
Cited by 28 publications
(17 citation statements)
references
References 160 publications
(113 reference statements)
1
15
0
Order By: Relevance
“…Computational screening of hundred thousands of natural compounds predicted Tinosorb as the top subnanomolar binding lead to SLSF-residues 1 . The Tinosorb's preferential binding to SLSF-residues, 3-arms-star-shaped molecular structure 3 and crossbinding the inner part of the SLSF-residue α-helices, together with the existence of side and central top-to-bottom surface-accessible cavities to SLSF-residues at the S wild-type prefusion state, suggested that Tinosorb may experimentally crossbind S-SLSF in vitro and show binding-dependent biological activities. Tinosorb's crossbinding of the inner space of the S-SLSF 3x3 α-helices could stabilize prefusion states blocking fusion and infection, similarly to what has been previously described for PP mutations of the 986 KV residues [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…Computational screening of hundred thousands of natural compounds predicted Tinosorb as the top subnanomolar binding lead to SLSF-residues 1 . The Tinosorb's preferential binding to SLSF-residues, 3-arms-star-shaped molecular structure 3 and crossbinding the inner part of the SLSF-residue α-helices, together with the existence of side and central top-to-bottom surface-accessible cavities to SLSF-residues at the S wild-type prefusion state, suggested that Tinosorb may experimentally crossbind S-SLSF in vitro and show binding-dependent biological activities. Tinosorb's crossbinding of the inner space of the S-SLSF 3x3 α-helices could stabilize prefusion states blocking fusion and infection, similarly to what has been previously described for PP mutations of the 986 KV residues [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%
“…The majority of the Tinosorb-similar leads contained chemotypes having a central Triazine core (N at 1,3 and 5 positions), with 3 hydroxyl-phenyl groups linked to the core carbons (such structures have been called star-shaped molecules) 2 . Additional structural variations in the leads consisted in different fragments linked to the C1 of each phenyl group forming star-shaped molecules > 620 Daltons (F+TTT, Fragment-Trihydroxyl-Triphenyl-Triazine).…”
Section: Resultsmentioning
confidence: 99%
“…Computational screening of ~130000 natural compounds predicted lower leads to wild-type SLSF trimers rather than to monomers and to other PP mutated conformers. Preferential binding to the SLSF trimers in the low nM range, its star-shaped 3-fold symmetric molecular structure 2 and its fitting to the inner part of the 3x3 SLSF α-helices, together with the existence of side and top-bottom surface-accessible cavities in the prefusion S wild-type trimer, suggested that Tinosorb may show binding and bindingdependent biological activity. Hypothetically, Tinosorb's cross-binding of the inner space of the S-SLSF 3x3 α-helices could stabilize its prefusion states to inhibit fusion, similarly to PP mutations [3][4][5] .…”
Section: Introductionmentioning
confidence: 99%
“…Computational screening of hundred thousands of natural compounds predicted Tinosorb as the top subnanomolar binding lead to SLSF-residues 1 . The Tinosorb's preferential binding to SLSF-residues, 3-arms-star-shaped molecular structure 3 and crossbinding the inner part of the SLSF-residue α-helices, together with the existence of side and central top-to-bottom surface-accessible cavities to SLSF-residues at the S wild-type prefusion state, suggested that Tinosorb may experimentally crossbind S-SLSF in vitro and show binding-dependent biological activities. Tinosorb's crossbinding of the inner space of the S-SLSF 3x3 α-helices could stabilize prefusion states blocking fusion and infection, similarly to what has been previously described for PP mutations of the 986 KV residues [4][5][6] .…”
Section: Introductionmentioning
confidence: 99%